2018
DOI: 10.1016/j.yhbeh.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated aggressive behavior in male mice with thyroid-specific Prkar1a and global Epac1 gene deletion

Abstract: Alterations in circulating thyroid hormone concentrations are associated with several psychological and behavioral disorders. In humans, behavioral disorders such as anxiety, depression, and attention-deficit hyperactivity disorder can be associated with thyroid disease. The Tpo-Cre;Prkar1a;Epac1 (R1A-Epac1KO) mice, originally bred to investigate the role of exchange protein directly activated by cAMP (Epac1) in follicular thyroid cancer, displayed self-mutilating and aggressive behaviors during casual observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
2
3
0
Order By: Relevance
“…Previous studies have reported that EPAC1 −/− mice are protected against inflammatory (Eijkelkamp et al, 2013, Singhmar et al, 2016, Wang et al, 2013) and neuropathic pain (Eijkelkamp et al, 2013, Singhmar et al, 2018), but possible roles for EPAC2 are unknown. We show that EPAC2 −/− mice do not differ from their wild-type counterparts for general behavioral functions as found previously for EPAC1 −/− mice (Russart et al, 2018). While our results are in accord with previous publications (Lee et al, 2015, Srivastava et al, 2012), another study reported that EPAC2 −/− mice exhibit signs of anxiety (Zhou et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have reported that EPAC1 −/− mice are protected against inflammatory (Eijkelkamp et al, 2013, Singhmar et al, 2016, Wang et al, 2013) and neuropathic pain (Eijkelkamp et al, 2013, Singhmar et al, 2018), but possible roles for EPAC2 are unknown. We show that EPAC2 −/− mice do not differ from their wild-type counterparts for general behavioral functions as found previously for EPAC1 −/− mice (Russart et al, 2018). While our results are in accord with previous publications (Lee et al, 2015, Srivastava et al, 2012), another study reported that EPAC2 −/− mice exhibit signs of anxiety (Zhou et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…As previously shown for EPAC1 −/− mice (Russart et al, 2018), we first confirmed that EPAC2 −/− mice did not exhibit major differences from wild-type mice in general behavioral functions (Lee et al, 2015, Srivastava et al, 2012) but see also (Zhou et al, 2016): anxiety, as tested by time spent in the open arms of the elevated plus maze (EPM); motor coordination, as tested by latency to fall off the rotarod; and general activity level, as tested by average velocity within an activity box (Table 1). In addition, von Frey mechanical sensitivity tests and Hargreaves heat sensitivity tests were used to assess basal mechanical and thermal sensitivity, respectively.…”
Section: Resultssupporting
confidence: 74%
“…These findings suggest that the mice displayed impaired spatial working memory, as evidenced by their reduced time and fewer visits to the novel arm [55]. Additionally, the administration of miR-669g was found to induce shorter attack latency and more attacks, resulting in exaggerated aggressive behavior in mice [29]. Interestingly, these findings suggest that the behavioral inhibition resulting from TPH2 impairment is mediated by miR-669g, which exhibits a similar behavioral phenotype to that observed in rodents with 5-HT depletion.…”
Section: Discussionmentioning
confidence: 88%
“…the Y-maze test (spatial working memory), and the NOR test (recognition memory) for measures of learning and memory functions [27], while aggression was measured using the resident-intruder test [29]. In the open field test, mice that spent more time in the central area of the box tended to exhibit reduced anxiety-like behavior [53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation